2018
DOI: 10.2147/dmso.s157348
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and oxidative stress in children with type 1 diabetes mellitus

Abstract: BackgroundThe early imbalances of trace elements in type 1 diabetes (T1D) may cause disturbance of glucose metabolism and more oxidative stress that may enhance the development of insulin resistance and diabetic complications. We aim to evaluate the serum level of selenium (Se), zinc (Zn), magnesium (Mg), and copper (Cu), the degree of oxidative stress and evaluate their relations to glycemic control in children with T1D.MethodsA case–control study which included 100 diabetic children and 40 healthy children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
2
19
0
3
Order By: Relevance
“…Copper containing enzymes and transcription factors are essential for cellular integrity, energy production, signalling, proliferation, oxidation and radiation defence. Research concerning acute or chronic toxicity of copper due to its deficiency or excess is growing rapidly and interest in the subject is pervasive [ 4 12 ]. Nevertheless, the pertinent redox status-dependent chelation [ 13 19 ] and regulatory mechanisms [ 20 32 ] are still being elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Copper containing enzymes and transcription factors are essential for cellular integrity, energy production, signalling, proliferation, oxidation and radiation defence. Research concerning acute or chronic toxicity of copper due to its deficiency or excess is growing rapidly and interest in the subject is pervasive [ 4 12 ]. Nevertheless, the pertinent redox status-dependent chelation [ 13 19 ] and regulatory mechanisms [ 20 32 ] are still being elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…4), кото рый характерен для всех типов клеток [9]. Геном человека включает 25 Se -H элемента в условиях отсутствия защиты тиреоцитов от окислительного повреждения приводит к нарушению их клеточной целостности, изменению метаболизма гормонов ЩЖ и активности биотрансформирующих ферментов, усилению токсического действия тяжелых металлов, повышению концентрации глутатиона в плазме. К основным селенсодержащим белкам, локализующимся в больших количествах в ЩЖ, относятся ферменты -GPX, ID, тиоредоксинредуктаза (TXNRD), селенопротеин (таблица, рис.…”
Section: селенсодержащие белкиunclassified
“…Недавнее исследование типа "случай-контроль", проведенное на австралийской популяции, также продемонстрировало, что уровни селена в сыворотке крови ниже у пациентов с ОГ по сравнению с пациентами с БГ без орбитопатии [25].…”
Section: эндокринная офтальмопатияunclassified
“…The results showed that the intracellular GPx and SOD2 enzyme activities were inhibited significantly in FGSCs after GANT61 treatment; the results also showed a GSH decrease and an MDA increase ( Fig. 6a-d), indicating that the blockage of Hh signaling damaged FGSCs through activating oxidative stress [56,57]. In addition, DHR, an examination index of ROS that presents green fluorescence when it is oxidized in mitochondria, was obviously enhanced as shown by an increase in green fluorescence in the GANT61 group (Fig.…”
Section: Discussionmentioning
confidence: 93%